2017
DOI: 10.3329/nimcj.v8i1.32390
|View full text |Cite
|
Sign up to set email alerts
|

An Association of Serum ferritin and SGPT Level in Transfusion dependent Thalassaemia major Patients-A Cross Sectional Study

Abstract: Background : The Thalassaemia is an inherited haemoglobulin disorder causes hemolytic anemia which usually requires life-long blood transfusion therapy. Therefore transfusion dependent thalassaemia major patients suffer from the effect of deposition of excess iron in the liver, heart and endocrine glands.Objective : The aim of present study was to find out the association of serum ferritin and SGPT in transfusion dependent thalassaemia major patient.Methodology : This cross sectional study was carried out in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…While the SGPT level has a significance value of 0.02 and a positive correlation coefficient value of 2.89, serum ferritin levels have a significant relationship with the strength of a weak relationship and are in the same direction as serum SGPT levels (Table 6). These results follow the research of Parvin F et al ( 2016), which reported a significant positive correlation (r = 0.259; p = 0.006) between serum ferritin and ALT [29]. Different results were reported by Patel SA et al (2018) in terms of the relationship between serum ferritin and SGOT; they conducted a study of 70 subjects with criteria aged 2 to 14 years, had undergone > 5 blood transfusions and had received oral chelation therapy for more than one year.…”
Section: Resultssupporting
confidence: 92%
“…While the SGPT level has a significance value of 0.02 and a positive correlation coefficient value of 2.89, serum ferritin levels have a significant relationship with the strength of a weak relationship and are in the same direction as serum SGPT levels (Table 6). These results follow the research of Parvin F et al ( 2016), which reported a significant positive correlation (r = 0.259; p = 0.006) between serum ferritin and ALT [29]. Different results were reported by Patel SA et al (2018) in terms of the relationship between serum ferritin and SGOT; they conducted a study of 70 subjects with criteria aged 2 to 14 years, had undergone > 5 blood transfusions and had received oral chelation therapy for more than one year.…”
Section: Resultssupporting
confidence: 92%